Obese patients' dissatisfaction with weight, body image and clinicians' interaction at a district hospital; Gauteng - Buhendwa Kanozire; Deidré Pretorius (AOSIS, 2023)
Background: Obesity in South Africa has created a public health crisis that warrants a multilevel intervention. However, patients' perceptions and clinicians' challenges hinder the management of obesity in primary care. Aim: The study aimed to assess obese patients' dissatisfaction with weight and body image and their perspectives on interaction with clinicians regarding obesity management in a primary care setting. Setting: Outpatient department of Dr Yusuf Dadoo District Hospital. Methods: Cross-sectional study of 213 adult obese patients. A semi-structured questionnaire, a body image assessment tool and patients' medical records were used for data collection. Results: The study found that, contrary to popular belief, obese patients were dissatisfied with their weight (78.9%) and body image (95.3%). Many felt comfortable while discussing weight reduction with clinicians, although 37.1% reported never engaging with a doctor and 62.9% never interacted with a nurse on the subject. Only 6% reported receiving adequate information on weight reduction measures and 19.7% were followed-up. Clinicians' advice was mainly associated with patients' high body mass index and waist circumference. Doctors were less likely to recommend weight reduction to employed obese women, while nurses were more likely to engage Zulu-speaking patients. Patients were more likely to be followed up if they were young and excessively obese. Conclusion: The study found that most obese patients were dissatisfied with their weight and body image and perceived their interaction with clinicians regarding obesity management as inadequate. Contribution: The study provides an angle of view of challenges in obesity management from patients' perspectives.